THE EFFECT OF A MODERATE-INTENSITY AEROBIC TRAINING PROGRAM ON THE SLEEP QUALITY, BMI, AND WEIGHT IN NON-ACTIVE PEOPLE WITH TYPE 2 DIABETES - Vahid Bakhshalipour,; Siavash Khodaparast Sareshkeh,; Majid Keramati Moghadam,; Maryam Falah Kazemi, (Sport Scientific And Practical Aspects, 2025)
Diabetes Mellitus has imposed a large economic burden on society in recent decades. It is a group of metabolic diseases characterized by hyperglycemia resulting from defects in insulin secretion, insulin action, or both. The daily inactivity, poor lifestyle, and prevalence of obesity are important and effectiveness factors in the incidence of type 2 diabetes. The purpose of this study was to examine the effect of a moderate-intensity aerobic training program on the sleep quality, BMI, and weight in non-active people with type 2 diabetes.The method of this study was semi empirical. The statistical population of this study was 30 patients with Type 2 Diabetes. Kolmogorov-Smirnov test was used to determine the data normality. The collected data were classified by descriptive statistical methods and were analyzed by independent and dependent T-test (α≤ 0.05). The results of this study showed that there was no significant relationship between the sleep quality and age, duration of diabetes, education, and marital status. But there was a significant relationship between sleep quality and without history of sport, weight, and BMI changes. Diabetes is an effective predictor for the reduction of sleep quality and there is a relationship between the sleep and obesity so that the results of this study showed that a moderate-intensity aerobic training program can be an effective treatment for sleep disorders and obesity in non-active people with type 2 diabetes.